La Coroplastica Greca. Metodologie per lo studio di produzioni, contesti e immagini - Jaimee Uhlenbrock (Les Carnets de l’ACoSt)
From May 27 to June 1, 2013, the First International Summer School on Greek Coroplastic Studies was held in Catania, Sicily. Organized by ACoST Executive Committee member Antonella Pautasso, project director at IBAM-CNR, Catania, and Ambra Pace of the University of Messina, with the support of Mario Cottonaro of the University of Catania and Vanessa Chillemi of the University of Messina, this 6-day event was called La Coroplastica Greca. Metodologie per lo studio di produzioni, contesti e immagini. It was developed mainly as a specialized course for university students wishing to conduct research on Greek terracotta objects, or simply to learn more about the study of Greek terracottas, although more advanced researchers also were enrolled. The main thrust of the week was to provide 34 participants (Fig. 1) with a total immersion in coroplastic studies by means of lectures and hands-on workshops (Figs. 2-3). In addition, the volumePhilotechnia. Studi sulla coroplastica della Sicilia greca, edited by Marina Albertocchi and Antonella Pautasso, IBAM CNR 5, Catania, 2012, was officially presented.